98.9k views
2 votes
Make m the subject of the formula. r=5m^2-n​

User Pradi KL
by
4.4k points

2 Answers

4 votes

Answer:

Explanation:

r = 5m² - n

Add n to both sides

r + n = 5m² - n +n

r + n = 5m²

Divide both sides by 5

(r+n)/5 = 5m²/5

(r + n)/5 = m²

Take square root ,


\sqrt{(r + n)/(5)} =\sqrt{m^(2)} \\\\\sqrt{(r + n)/(5)}=m\\\\\\m=\sqrt{(r + n)/(5)}

User Nexii Malthus
by
6.5k points
7 votes

Answer:

The answer is


m = \sqrt{ (r + n)/(5) }

Explanation:


r = 5 {m}^(2) - n

To make m the subject send n to the left side of the equation

That's


{5m}^(2) = r + n

Divide both sides by 5

We have


\frac{ {5m}^(2) }{5} = (r + n)/(5)


{m}^(2) = (r + n)/(5)

Find the square root of both sides to make m stand alone

That's


\sqrt{ {m}^(2) } = \sqrt{ (r + n)/(5) }

We have the final answer as


m = \sqrt{ (r + n)/(5) }

Hope this helps you

User Killroy
by
5.4k points